Effect of shaft stiffness and sole flexibility on perceived comfort and the plantar pressures generated when walking on a simulated underground coal mining surface. (April 2020) - Dobson, Jessica A.; Riddiford-Harland, Diane L.; Bell, Alison F.; Wegener, Caleb; Steele, Julie R.
Abstract: The structural features of work boots worn by underground coal miners affect comfort, foot motion and, in turn, loading of the plantar surface of miners' feet. Although shaft stiffness and sole flexibility appear to be boot design features that could influence perceived comfort and plantar pressures, no study has systematically altered these boot design features to truly understand how they affect these parameters. This study aimed to systematically investigate the effect of changes to shaft stiffness and sole flexibility on perceived comfort and plantar pressures when 20 males walked on a simulated gravel coal mining surface under four different work boot conditions. There were no significant effects of shaft stiffness or sole flexibility on perceived comfort. However, shaft stiffness and sole flexibility each significantly affected the plantar pressures generated under the medial midfoot, heel, middle metatarsals and hallux and, in combination, affected plantar pressures generated beneath the lateral midfoot, medial and lateral metatarsals and lesser toes. Participants preferred a boot with a flexible shaft combined with a stiff sole, citing properties such as fit, moveability, walking effort and support to explain why they perceived one boot as more comfortable than another. We therefore recommend that underground coal mining work boots should be designed to incorporate different flexibility and stiffness between the shaft and sole of the boot to optimise foot movement and, in turn, walking efficiency. Highlights: Structural features of work boots can affect comfort and plantar pressures. 20 males walked across a simulated gravel mining surface under 4 boot conditions. Shaft stiffness or sole flexibility had no effect on perceived comfort. Future designs need different flexibility and stiffness between the shaft and sole.